Resenha do livro de Fábio Portela Lopes. Constitution: The Darwinian Evolution of a Societal Structure - Elmauer, Douglas (2022)
Resenha: Almeida, Fábio Portela Lopes de (2020). Constitution: The Darwinian Evolution of a Societal Structure. 1. ed. Baden-Baden: Nomos, 2020.